Studi Komparatif Program Visual Dinamis untuk Pembelajaran Algoritma dan Pemograman Berorientasi Objek - Kursehi Falgenti (Indonesian Society of Applied Science, 2020)
As beginners, many first-year students have difficulty understanding object-oriented programming material. To help students learn algorithmic and object-oriented programming material researchers have developed visual programming (PV). Visual programming is a tool to facilitate learning programming. The concept of learning to use PV visualizes the work processes of algorithms and programming. This research aims to compare three dynamic PV tools for object-oriented learning programming that are the most studied. To determine the PV to be compared, a survey was conducted in an online journal database, such as IEEE explore, ACM, and several well-known online publishers. From the survey results, three dynamic PVs were chosen, most widely discussed, namely Jeliot 3, Ville and Jive. All three tools are installed and studied. Comparison results show that each dynamic PV has advantages on certain characteristics. The instructor can choose visual programming by considering the advantages of each PV.